(untitled) (Neo Science Peer Reviewed Journal, 2023)
In the literature of the following years, the freedom to truly create, speak and tell the truth has developed widely. Much progress has been made in Uzbek prose in this regard. In prose, new works are being created based on the centuries-old experience of national literature and researches in world literature. One such experienced prose master is Isajon Sultan. The topics described in his novels and stories, which are well known to today’s readers, such as "Munojot", "Aydinbuloq", "Baqiy Darbadar", "Azod", "Bogi Eram", are remarkable for their variety, relevance, and, moreover, their vitality. In this article, Isajon Sultan’s ability to create portraits, use landscapes and artistic details, and the issues of imagery, symbols and symbolization, which are the reflection of mastering life, are researched.